Effect of feed restriction on nutrient utilization, growth and metabolic profile in crossbred calves - OJHA, B K; DUTTA, NARAYAN; PATTANAIK, A (The Indian Journal of Animal Sciences, 2018)
Present study elucidated the effect of feed restriction on growth, nutrient utilizationand metabolic profile in crossbred calves. Eighteen crossbred male calves (Bos Taurus x Bos indicus) of about 4–6 months age and 85.7±5.6 kg body weight were randomly divided into 3 groups (Control, T–15 and T-30) of 6 each in completely randomised design. The calves in control group were fed ad libitum as per predicted requirement; while in group T-15 and T-30 calves were fed 15 and 30% restricted diets of predicted requirements. Daily intake of DM and OM was significantly (P